An Overview of Foreign Currency Exposure - HARRIS, Peter; KAUR, Simran (Asian Journal of Empirical Research, 2013)
Foreign exchange exposure is defined as the assessment of potential of a firm’s profitability, net cash flow, and market value to change due to unpredictable changes of foreign exchange rates, which can be financially unfavorable to the global firm. This paper discusses the three various types of major foreign exchange exposure which are, translation, transaction, and economic; the risks associated with each exposure, and how to minimize specific currency risks.